Seeking Help from Faith Healers among Iraqi Patients with Obsessive – Compulsive Disorder - Al-Hemiary, Nesif J.; Al-Hasnawi, Salih M. (Journal of the Faculty of Medicine Baghdad, 2010)
Background: Faith healing is common in Arab culture. Obsessive-compulsive disorder is linked to religious beliefs and this can affect its management as patients may seek help from faith healers rather than mental health professionals.Patients and methods: Patients who received a diagnosis of OCD according to DSM-IV-TR completed a questionnaire containing questions about age, gender, marital state, residence, income, level of education, and occupation. Also, data was collected on help-seeking from a faith healer and on religiosity. The data was analyzed by using the statistical package of the social sciences (SPSS).Results: 58.5% of OCD patients had sought help from faith healers and this was significantly associated with being religious (p value .003). There was no association with other variables.Conclusion: Iraqi mental health professionals should be aware of patient’s experience of faith healing as this is common among OCD patients. The findings also raise interesting questions regarding the need for a dialogue between health professionals and faith healers in the interest of providing optimal care to OCD patients.